OPTIMALISASI PENCATATAN KEUANGAN DAN TRANSFORMASI PEMBAYARAN NON TUNAI (QRIS) PADA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) SLAMET CERAMIC KASONGAN BANTUL - Lisa Nining Lestari; Zaenal Wafa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Field Work Practice (PKL) is one form of community service activity that aims to implement students’ knowledge and skills directly in the business sector. This PKL activity was carried out at the MSME Slamet Ceramic located in Kasongan, Bantul, which is engaged in the production and sale of pottery crafts. The purpose of this community service activity is to optimize the financial recording of the business and to support the transformation toward non-cash payments through the implementation of the Quick Response Code Indonesian Standard (QRIS), in order to improve financial governance and the competitiveness of MSMEs. The methods used in this program include initial observation to identify problems, mentoring and training in simple financial recording, as well as the socialization and implementation of a QRIS-based non-cash payment system. The results show that optimizing financial recording helps MSME owners better understand the financial condition of their business in a more systematic manner, separate personal and business finances, and facilitate financial decision-making. In addition, the implementation of QRIS has a positive impact in the form of increased transaction efficiency, a wider range of payment options for customers, and support for the digitalization process of MSMEs.